The Correlation Between Students’ Speaking Skill and Their Participation in the English Club of SMA negeri 7 Pekanbaru - Rayhanah Maulani Raghdah; Pahmi Pahmi; Siti Niah (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
Purpose – This study investigates the correlation between students' participation in English clubs and their speaking skills among high school students in Pekanbaru City. Speaking is a crucial English language skill that learners must master, as it plays a significant role in effective communication. Fluency in speaking is often used as a measure of language acquisition quality. However, learners face several challenges in developing their speaking skills, including nervousness, lack of strategic communication, and insufficient practice opportunities. English clubs serve as platforms to enhance students' speaking skills by providing engaging and interactive environments.Design/methods/approach – A quantitative research approach was employed, with data collected through questionnaires and speaking tests. The study involved 13 students from SMA Negeri 7 Pekanbaru who participated in the English club. Statistical analysis using SPSS 25, specifically Pearson's product-moment correlation coefficient, was conducted to determine the relationship between the two variables.Findings – There is a significant positive and strong correlation (r = 0.961, p < 0.01) between participation in the English club and students' speaking skills. This suggests that students actively engaging in English club activities tend to demonstrate better speaking proficiency. The study highlights the effectiveness of English clubs as an extracurricular program that fosters students' confidence, communication skills, and language proficiency through various activities such as storytelling, speeches, and debates.Research implications/limitations – The study is limited by the small sample size of 13 students, which may affect the generalizability of the findings to a larger population. This research contributes to the understanding of how English clubs support language learning and encourages further implementation of such programs to enhance students' speaking abilities. Future studies may explore additional factors influencing speaking proficiency and the long-term impact of English club participation on students' overall language development.